Using AI in Academic Writing and Research - Haber, Eldar. author. (orcid)0000-0002-1513-551X Link aut Link
IX, 147 p.
Keywords: This book comprehensively explores how AI tools can revolutionize academic writing, research, grant proposals, and educational practices. With a focus on practical applications, ethical considerations, and future trends, the book serves as an indispensable roadmap for academics, researchers, and educators eager to integrate AI into their work. Whether you're looking to enhance your research capabilities, craft compelling grant proposals, personalize learning experiences, or lead your institution into the future, this book provides the insights and tools necessary to navigate and shape the AI-enhanced landscape of academia. It demonstrates how to redefine scholarly work with cutting-edge AI innovations through real-life, practical examples, yet keeping the level of generalization high enough to keep it relevant for a few years. By balancing specific, actionable insights with broader perspectives, this book equips readers to not only adapt to but actively influence the evolving role of AI in higher education, research, and funding acquisition, ensuring its value as a resource both now and in the coming years. Eldar Haber is an Associate Professor at the Faculty of Law, University of Haifa, and the co-director of the Haifa Center for Law & Technology (HCLT). Dariusz Jemielniak is a Full Professor and head of the Management in Networked and Digital Environments (MINDS) department at Kozminski University and a faculty associate at Berkman-Klein Center for Internet and Society, Harvard University. Artur Kurasiński is an entrepreneur, creator, investor, observer, and critic of phenomena related to technology. Aleksandra Przegalińska is a philosopher and data scientist. She is the Vice-Rector of Kozminski University and Senior Research Associate at Harvard University. She is a co-founder of the AI in Management program and was recently a Research Fellow at MIT's Center for Collective Intelligence.